The Effect of Problem-Based Learning Assisted by Video Animation on Students' Self-Efficacy and Creative Thinking Ability - Niswatun Hasanah; Mochamad Yus Cholily; Mohammad Syaifuddin (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
Students' creative thinking skills and different self-efficacy cause weaknesses for students in solving problems presented in learning mathematics. This study aimed to determine how implementing video-assisted problem-based learning affects students' self-efficacy and creative thinking abilities. This research method uses quantitative with a quasi-experimental research design. The study sample population of class XII IPA 2 students consisted of 34 students in the experimental class and 30 students in the class XII IPA 1 and control classes. Statistical analysis of N-Gain score of self-efficacy sig 0,014 0,05 and creative thinking skills sig = 0,003 0,05. The study results show significant differences in self-efficacy and creative thinking skills of students in the experimental class compared to the control class. This indicates the enormous difference in gains between experimental and control classes. Thus, the influence of problem-based learning assisted by video animation on students' self-efficacy and creative thinking abilities is very large. Problem-based learning model with animated videos can organize students in informing learning objectives so that students have the motivation to be actively involved in problem-solving activities.Kemampuan berpikir kreatif siswa dan self eficacy yang berbeda menyebabkan kelemahan bagi siswa untuk memecahkan masalah yang disajikan dalam pembelajaran Matematika. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh penerapan pembelajaran berbasis masalah berbantuan video animasi terhadap kemampuan efikasi diri dan berpikir kreatif siswa. Metode penelitian ini menggunakan kuantitatif dengan desain penelitian quasi experiment. Sampel penelitian ini adalah siswa kelas XII IPA 2 terdiri dari 34 siswa sebagai kelas eksperimen dan siswa kelas XII IPA 1 terdiri 30 siswa sebagai kelas pembanding. Analisis statistik tes berpikir kreatif memperoleh nilai signifikasi = 0,003 0,05 and efikasi diri sebesar 0,014 0,05. Hasil penelitian menunjukkan perbedaan yang signifikan antara berpikir kreatif dan efikasi diri siswa pada kelas eksperimen dan kelas kontrol. Dengan demikian bahwa pengaruh penerapan pembelajaran berbasis masalah berbantuan video animasi terhadap efikasi diri dan kemampuan berpikir kreatif siswa sangat besar. Model pembelajaran berbasis masalah dengan video animasi dapat mengorganisasikan siswa dalam menginformasikan tujuan pembelajaran sehingga siswa memiliki motivasi untuk terlibat aktif dalam kegiatan pemecahan masalah.